Cortical mechanisms of binocular stereoscopic vision. - Parker, A; Cumming, BG (2001)
The early neurophysiology of binocular vision is largely dominated by measurements of disparity selectivity in cortical neurons in various visual areas. Incisive progress has been made by the intensive study of the mechanism of disparity selectivity of V1 in cortical neurons and the development of a number of tests for the involvement of single neurons in the perception of stereoscopic depth. The picture that now emerges is that cortical area V1 must be a preliminary processing stage for the analysis of stereoscopic depth, whereas some of the extrastriate areas may actually be responsible for the generation of neuronal signals that underlie the perception of binocular depth.